Serum Levels of 25-Hydroxyvitamin D in Chronic Plaque Psoriasis - Jha, Ayush; Singh Basukala, Manisha; Shrestha, Rima; Dawadi, Roji (Nepal Journal of Dermatology, Venereology & Leprology, 2023)
Background: Psoriasis is an immune mediated inflammatory disease that involves the innate and acquired arm of immunologic system. The regulatory role for vitamin D in immune system is suggested by presence of vitamin D receptors on activated lymphocytes and suppressive or inhibiting effect of 1,25-dihydroxyvitamin D in different autoimmune diseases. Hence, the current proposed study aims to study the 25-hydroxyvitamin D status of patients with psoriasis. Objective: The primary objective of this study was to analyze the 25-hydroxyvitamin D status of patients with chronic plaque psoriasis in comparison to healthy control subjects. Materials and Methods: A comparative cross-sectional study, including forty patients with chronic plaque psoriasis and forty age- and sex-matched control subjects, was conducted from April 2021 to December 2022, at our dermatology department. After informed consent, all patients were subjected to detailed clinical and anthropometric examination. Serum concentration of 25-hydroxyvitamin D was evaluated in chronic plaque psoriasis cases and healthy control subjects. Data was be analyzed as per standard statistical protocol. Results: The mean serum 25-hydroxyvitamin D level in psoriatic group and control group were 18.02 (±SD 9.82) ng/ml and 24.47 (±SD 6.77) ng/ml, respectively. (p=.001) Serum 25-hydroxyvitamin D was negatively correlated with Psoriatic area and severity index (PASI) score (r=-.11). However, this correlation was not significant (p=.493). Conclusion: Serum 25-hydroxyvitamin D levels were significantly lower in psoriatic patients than in control subjects.